Perlindungan Hukum Bagi Wajib Pajak Kurang Bayar Pajak - Samudra, Arya Dhuta Biru; Mardijono, H.R Adianto (CV. Era Digital Nusantara, 2025)
This study aims to examine the forms of legal protection provided to taxpayers who experience underpayment of taxes within the Indonesian tax system. Underpayment issues may arise due to a lack of knowledge, administrative errors, or differences in interpretation between the taxpayer and the tax authorities. These circumstances often lead to significant legal consequences, such as administrative or criminal sanctions. Using a normative juridical approach, this study analyzes the provisions of the General Provisions and Tax Procedures Law (UU KUP) and its implementing regulations, including the mechanisms of objection, appeal, and other legal remedies available to taxpayers. The results show that although legal protection mechanisms for taxpayers with underpaid taxes are in place, practical challenges remain, such as information asymmetry, a heavy burden of proof, and limited access to legal assistance. Therefore, regulatory reforms and improved access to legal protection are necessary to ensure a fair, transparent, and legally certain tax system for taxpayers.